PENINGKATAN KETERAMPILAN MENGUBAH PUISI MENJADI PROSA MENGGUNAKAN MODEL ICARE SISWA KELAS VI SD - Ilmasari, Reka; Taufina, Taufina; Mayarnimar, Mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research is to describe the improvement of turn poetry into prose skill by using ICARE models at grade VI student of Elementary School. The type of research is PTK by using qualitative and quantitative approach. This research was conducted at SD Negeri 29 Pitameh, Padang city with a total of 21 students consisting of 14 male students and 7 female students. The result of the narrative writing skill in the pre-writing at cycle I 66,67 (C) increases on cycle II 82,74 (SB). The writing phase in the first cycle 49,60 (K), increased in the second cycle 79,36 (B), the post-writing phase cycle I 57,54 (C) increases in cycle II 82,54 (B ).                                                                            Keywords: Increased, poetry, prose, ICARE model.